Analisis Perbandingan Biaya Supply Chain Logistik Jepang dan Indonesia: Tinjauan Terhadap Aspek Etika, Transparansi, dan Keberlanjutan - Hasana, Nabila; Rahma Malika Ayu, Alya; Hajj Arham, Muhammad; Aprilian Pratama Kusuma, Revanza; Farida Adi Prawira, Ida (Jurnal Sosial-Politika, 2025)
Logistics costs in Indonesia remain relatively high compared to Japan, despite both being archipelagic countries. The key differentiating factor lies in supply chain efficiency and procurement systems. Japan has optimized its supply chain through the adoption of technologies such as the Internet of Things (IoT), big data analytics, and artificial intelligence (AI), which enhance transparency and operational efficiency. Additionally, Japan’s e-procurement system and Just-in-Time (JIT) approach minimize procurement time and costs. The procurement process in Japan is also supported by strict supplier evaluations, supply chain diversification, and the implementation of sustainable practices such as green procurement and the circular economy. In contrast, Indonesia still faces challenges such as complex bureaucracy, limited infrastructure, and a lack of digital integration in supply chain management. By comparing logistics and procurement strategies between Indonesia and Japan, this study identifies strategic steps that can be implemented to improve supply chain efficiency in Indonesia, reduce logistics costs, and strengthen national economic competitiveness.